Types of moral hazards and its effects on insurance marketing and health system - M Soofi; M Bazyar; A Rashidian (Tehran University of Medical Sciences, 2012)
Background: Insurance coverage has a tendency to alter the consumer and provider's behavior. Moral hazard is a serious problem in all risk pooling systems, such as insurance and taxes-based financial systems that cause negative consequences as increased costs in the health system. Therefore we decide, at this review article, to discuss about moral hazard, in different classifications and effects on the insurance marketing and health system. Materials & Methods: This is a review article. Relevant materials selected from published articles, studies, and sites. The databases of Medline, Web of Science, Science Direct, Google Scholar, and Springer were explored to use the key words of moral hazard and health insurance. Results: Insurance covered individuals, knowing that their health expenditures will be reimbursed by insurance in the time of illness, and their demand medical services are more than un insurance covered individuals. On the other hand the providers have financial incentive to provide unnecessary and excess medical services. Different types of moral hazard like as ex ante and ex post moral hazard hidden information and hidden action moral hazard provider and consumer moral hazard may arise due to insurance coverage. These lead to negative consequences such as consumption of unnecessary care services, alteration of consumption pattern for inefficient use of resources, welfare loss, and an increase in the health expenditures. Conclusion: Studying and controlling the effects of moral hazards seems necessary to prevent unwelcome outcomes as well as misallocation of financial resources.